Aplikasi Sistem Manajemen Perpustakaan dengan Penerapan Pemrograman Berorientasi Objek - Angelina Jolie; Dedrick Dedrick; Raphael Kurniawan Sugeng; Winona Audrey Lee; Andik Yulianto (Telcomatics, 2022)
Library is one of the most important pillars to improve the quality of Indonesia’s education. Due to its importance for the next generation, the government tries to increase the establishment of schools and libraries so that the young generation can compete with people from another countries. However, the increasing number of libraries did not mean that the library service quality will become better. Many library systems in Indonesia still have not kept up with technology and still using the manual system, hence the management process and services are not effective. Because of that, this research is created for the purpose of producing a design for a library management application. The methods used in this research is split into multiple steps which is system planning, class diagram planning, MySQL database planning, and GUI planning. The following processes will produce a library management desktop application that is integrated to a database. With this application, processing, documenting, and deliverance of data can be done in more effective and efficient way.